Global multiplicity for parametric anisotropic Neumann (p,q)-equations - Papageorgiou, Nikolaos S.; Rădulescu, Vicenţiu D.; Repovš, Dušan D. (Topological Methods in Nonlinear Analysis, 2023)
We consider a Neumann boundary value problem driven by the anisotropic (p,q)-Laplacian plus a parametric potential term. The reaction is ``superlinear". We prove a global (with respect to the parameter) multiplicity result for positive solutions. Also, we show the existence of a minimal positive solution and finally, we produce a nodal solution.